MiR‐625‐5p/PKM2 negatively regulates melanoma glycolysis state. Issue 3 (30th November 2018) - Zhang, Hailin; Feng, Cheng; Zhang, Mingzi; Zeng, Ang; Si, Loubin; Yu, Nanze; Bai, Ming
Abstract: PKM2 plays an important role in cancer glycolysis, however, the link of PKM2 and microRNAs (miRNAs) in melanoma is still unclear. The study will investigate the role of miRNAs in regulating PKM2 mediated melanoma cell glycolysis. We found that high PKM2 expression in melanoma tissues and cell lines was positively associated with glycolysis. Further study indicated that miR‐625‐5p regulated PKM2 expression on mRNA and protein levels in melanoma cells. There was a negative relationship between miR‐625‐5p and PKM2 expression in the clinical melanoma samples. These findings provide an evidence that miR‐625‐5p/PKM2 plays a role in melanoma cell glucose metabolism. Abstract : PKM2 promoted melanoma cell glycolysis and drug resistance and demonstrated that miR‐625‐5p regulated PKM2 expression in melanoma cells. miR‐625‐5p is one of miRNAs involved in cancer cell glucose metabolism targeting PKM2; however, our data hopefully improve current understanding of the regulatory network of cancer metabolism and provide potential targets for the development of cancer therapeutic methods.